Stable HEV IgG seroprevalence in Belgium between 2006 and 2014. Issue 11 (12th July 2020) - Ho, Erwin; Schenk, Julie; Hutse, Veronik; Suin, Vanessa; Litzroth, Amber; Blaizot, Stéphanie; Herzog, Sereina A.; Verburgh, Vera; Jacques, Marjorie; Rahman, Abbas; Michielsen, Peter; Van Damme, Pierre; et al.
Abstract: Recent European studies suggest an emergence of hepatitis E virus (HEV) infection. We evaluated trends in birth cohort‐specific HEV seroprevalence and regional differences in Belgium. HEV IgG seroprevalence was analysed on national serum banks (1579 and 2087 samples for 2006 and 2014, respectively. Hepatitis E virus antigen was tested on positive samples. Observed data were modelled using a generalized additive model with a complementary log‐log link. No significant differences between birth cohorts or sexes were found. Modelling identified the individual's age and province as relevant factors. The probability of HEV seropositivity increases significantly with age. An estimated total of 434 819 (yearly rate of 54, 352) (sero‐)infections were found between 2006 and 2014. Overall, HEV IgG seroprevalences were 4.1% (64/1579, 95% CI 3.1‐5.1) and 5.8% (121/2087, CI 4.8‐6.9) in 2006 and 2014, respectively. Observed HEV antigen seroprevalence was 0.027% (1/3666) for the entire cohort. These results show stable HEV IgG seroprevalence in Belgium.